Recycling supercapacitors based on shredding and mild thermal treatment - Jiang, Guozhan; Pickering, Stephen J. (Elsevier, 2016)
Supercapacitors are widely used in electric and hybrid vehicles, wind farm and low-power equipment due to their high specific power density and huge number of charge–discharge cycles. Waste supercapacitors should be recycled according to EU directive 2002/96/EC on waste electric and electronic equipment. This paper describes a recycling approach for end-of-life supercapacitors based on shredding and mild thermal treatment. At first, supercapacitors are shredded using a Retsch cutting mill. The shredded mixture is then undergone thermal treatment at 200 °C to recycle the organic solvent contained in the activated carbon electrodes. After the thermal treatment, the mixture is roughly separated using a fluidized bed method to remove the aluminium foil particles and paper particles from the activated carbon particles, which is subsequently put into water for a wet shredding into fine particles that can be re-used. The recycled activated carbon has a BET surface area of up to 1200 m2/g and the recycled acetonitrile has a high purity.